Menumbuhkan Jiwa Minat Wirausaha Di Kalangan Mahasiswa Semester IV Fakultas Ekonomi Universitas Batanghari - Reni Devita; Pupu Sopini (Universitas Batanghari, 2020)
In order to grow a spirit of entrepreneurial interest in students of the faculty of economics, this must be supported by an entrepreneurial learning system, especially through cognitive, affective, and conative components. This occurs because interest can be formed through direct experience or memorable experiences that provide opportunities for individuals to practice, obtain feedback, and develop skills that lead to personal education and the expectation of satisfactory results. Apart from entrepreneurship education, interest in entrepreneurship is also influenced by family factors, especially parents, which have a strong impact on the choice of entrepreneurial interests and other social environments. Students of the Faculty of Economics have a leadership spirit that will be useful for managing business activities. Having a sociable nature will also provide opportunities to open and develop business access. The ease of accepting suggestions and criticism will provide opportunities for business innovation so that it continues to develop and compete fairly with other business actors. Apart from entrepreneurship education, other factors to foster students; entrepreneurial interest can be done through observations from their family and other social environments. Students whose status work has a huge influence on efforts to foster entrepreneurial interest because work experience can influence career choices by introducing ideas. new, build the necessary skills. Based on the results of research that has been carried out using the descriptive analysis method Fostering Entrepreneurial Interest Among Students in Semester IV, Faculty of Economics, Bangtanghari University, from the 6 indicators in this study it can be seen that the total score of each indicator is very high seen from the scale range, namely between 478.8 - 570. Thus, this research hypothesis can be accepted.